2011
DOI: 10.1007/s10162-011-0299-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Task-Relevant and Task-Irrelevant Feature Continuity on Selective Auditory Attention

Abstract: Past studies have explored the relative strengths of auditory features in a selective attention task by pitting features against one another and asking listeners to report the words perceived in a given sentence. While these studies show that the continuity of competing features affects streaming, they did not address whether the influence of specific features is modulated by volitionally directed attention. Here, we explored whether the continuity of a task-irrelevant feature affects the ability to selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 28 publications
7
42
0
Order By: Relevance
“…Their results suggested that relevant and irrelevant features tend to be bound together and, the greater the separation between sequential elements along the taskirrelevant dimension, especially pitch, the more interference it produced. Despite the differences in stimuli and task, our results appear to be broadly consistent with those of Maddox and Shinn-Cunningham (2012). Although the detrimental effect we found here was significant, it was surprisingly small.…”
Section: Discussionsupporting
confidence: 82%
“…Their results suggested that relevant and irrelevant features tend to be bound together and, the greater the separation between sequential elements along the taskirrelevant dimension, especially pitch, the more interference it produced. Despite the differences in stimuli and task, our results appear to be broadly consistent with those of Maddox and Shinn-Cunningham (2012). Although the detrimental effect we found here was significant, it was surprisingly small.…”
Section: Discussionsupporting
confidence: 82%
“…The conclusion about the efficacy of voice and location cues from the current study is based on the findings indicating that speech identification performance was much above chance when such cues were the only basis for selecting the target words (e.g., by randomizing the complementary variable in the non-syntactic word order conditions; cf. Best et al, 2008;Maddox and Shinn-Cunningham, 2012). The finding that there was a significant difference in performance observed between the two a priori cues under speech masking conditions, as indicated by the pooled analysis reported in the preceding section, suggests that they differed in the degree to which they aided speech stream selection.…”
Section: Discussionmentioning
confidence: 99%
“…These give information about the size and the sex of a speaker (Hillenbrand and Clark, 2009;Smith et al, 2007;Titze, 1989), and can also play an important role for the intelligibility of speech in adverse listening scenarios (Darwin et al, 2003;. Furthermore, continuity of these vocal characteristics influences speech recognition performance Kidd et al, 2008;Maddox and Shinn-Cunningham, 2012;Shinn-Cunningham et al, 2013), suggesting that F0 and VTL are used to perceptually construct a speech stream (Gaudrain et al, 2007;Tsuzaki et al, 2007) by linking successive segments of speech over time. Hence, grouping successive segments of speech with different vocal characteristics should be more difficult in comparison with grouping speech segments from the same voice, and if the grouping rule of the continuity percept is a prerequisite for the repair mechanisms of missing speech segments, the voice manipulations that cause a disruption at the indexical level should reduce phonemic restoration benefit.…”
Section: Introductionmentioning
confidence: 98%